2005
DOI: 10.1016/j.jvs.2005.04.016
|View full text |Cite
|
Sign up to set email alerts
|

Spinal cord ischemia after elective stent-graft repair of the thoracic aorta

Abstract: Perioperative hypotension (MAP <70 mm Hg) was found to be a significant predictor of spinal cord ischemia; hence, careful monitoring and prompt correction of arterial pressure may prevent the development of paraplegia. When the latter occurred, reduction of the CSF pressure by drainage was useful. Patients with a previous or synchronous abdominal aortic repair may also benefit from CSF drainage as a perioperative adjunct.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
160
1
6

Year Published

2010
2010
2022
2022

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 257 publications
(171 citation statements)
references
References 38 publications
(67 reference statements)
4
160
1
6
Order By: Relevance
“…9,35 The collateral network concept described by Griepp et al proposes the existence of extensive redundant spinal blood supply. However, in acute situations, such as surgical procedures, spinal perfusion is dependent on the gradient of arterial blood pressure and of cerebrospinal fluid.…”
Section: Influence Of Postoperative Spinal Cord Ischemiamentioning
confidence: 99%
See 1 more Smart Citation
“…9,35 The collateral network concept described by Griepp et al proposes the existence of extensive redundant spinal blood supply. However, in acute situations, such as surgical procedures, spinal perfusion is dependent on the gradient of arterial blood pressure and of cerebrospinal fluid.…”
Section: Influence Of Postoperative Spinal Cord Ischemiamentioning
confidence: 99%
“…However, in acute situations, such as surgical procedures, spinal perfusion is dependent on the gradient of arterial blood pressure and of cerebrospinal fluid. 35 Spinal cord ischemia is therefore correlated with perioperative episodes of hypotension and exclusion of the hypogastric artery as part of the collateral network.…”
Section: Influence Of Postoperative Spinal Cord Ischemiamentioning
confidence: 99%
“…Esta complicación se observa con mayor frecuencia en pacientes con endoprótesis que determinen coberturas largas de la aorta, siendo un punto crítico más de 20 cms, antecedente de cirugía aórtica abdominal previa, cierre del origen de la subclavia izquierda, ausencia de hipogástricas por disminución de circulación colateral [20][21][22] .…”
Section: Discussionunclassified
“…[21][22][23] The medullary vascularization from the lumbar and hypogastric arteries are important contributors in the risk of paraplegia. [24] Given this information, it is therefore advised by various authors [22,25] to perform eventual treatment of the abdominal and thoracic aorta in different interventions, so that a gradual establishment of a collateral medullary vascular circuit can be established. At this centre, in cases where a long segment of the thoracic aorta is planned to be covered and the hypogastric circulation is compromised, a preventive treatment is routinely performed.…”
Section: Neurological Complicationsmentioning
confidence: 99%
“…This risk rises further when coverage includes the region distal to T10. [22,25,29] The EUROSTAR [21] study reported a significantly increased incidence of paraplegia when three or more endograft segments were used (OR, 3.5; P =.043).…”
Section: Neurological Complicationsmentioning
confidence: 99%